A Survey on the Evaluation of Monosodium Glutamate (MSG) Taste in Austria - Emilia Iannilli; Emilise Lucerne Pötz; Thomas Hummel (Foods)
The umami taste is well validated in Asian culture but remains less recognized and accepted in European cultures despite its presence in natural local products. This study explored the sensory and emotional perceptions of umami in 233 Austrian participants who had lived in Austria for most of their lives. Using blind tasting, participants evaluated monosodium glutamate (MSG) dissolved in water, providing open-ended verbal descriptions, pleasantness ratings, and comparisons to a sodium chloride (NaCl) solution. Discrimination tests excluded MSG ageusia, and basic demographic data were collected. A text semantic-based analysis (TSA) was employed to analyze the emotional valence and descriptive content of participants’ responses. The results showed that MSG was predominantly associated with neutral sentiments across the group, including both female and male subgroups. “Sour” was the most frequent taste descriptor, while “unfamiliar” characterized the perceptual experience. Pleasantness ratings for MSG and NaCl were positively correlated, suggesting that overcoming the unfamiliarity of umami could enhance its acceptance and align it with the pleasantness of salt. These findings advance the understanding of umami sensory perception and its emotional and cultural acceptance in European contexts, offering valuable insights for integrating umami into Western dietary and sensory frameworks.